Forward Masking Additivity and Auditory Compression at Low and High Frequencies - Plack, Christopher J. (Springer-Verlag, 2003)

(untitled)
The additivity of nonsimultaneous masking can be used as a measure of nonlinearity in the auditory system. For example, two equally effective forward maskers should produce 3 dB of additional masking when they are combined, assuming linearity with respect to intensity. A combined effect greater than this (excess masking) indicates compression. In the present experiments, the signal was a 10-ms pure tone presented 20 ms after a 200-ms narrowband noise masker and/or immediately after a 20-ms narrowband noise masker. The signal frequency was 250, 500, or 4000 Hz. The signal threshold produced by combining two equally effective maskers was measured. At all three frequencies, little excess masking was observed for a signal 10 dB above absolute threshold, indicating linear additivity (no compression). At signal levels 30 dB above absolute threshold, excess masking was observed at all three frequencies. The estimated compression exponents were 0.29 at 250 Hz, 0.34 at 500 Hz, and 0.17 at 4000 Hz. In contrast with physiological studies on other mammals, the present results provide evidence for substantial compression at low frequencies in humans.